Hydrotalcite Supported on Polycaprolactone:Poly(methyl methacrylate) Fiber Membranes for Chlorogenic Acid Removal - Nascimento, Andressa Cristina de Almeida; Malafatti, João Otávio Donizette; Silva, Maria Luiza Lopes Sierra e; Moreira, Ailton José [UNESP]; Thomazi, Adriana Coatrini; Quaranta, Simone; Paris, Elaine Cristina (MDPI, 2025)
Polyphenols are organic molecules extracted from various fruits, such as coffee and citrus, that possess biological activity and antioxidant properties. However, the presence of polyphenols in the environment is hazardous to water quality and living health. Among a variety of water remediation methods, adsorption remains a staple in the field. Therefore, this work aims to develop porous polycaprolactone: poly(methyl methacrylate) (PCL:PMMA) membranes as a support for hydrotalcite immobilization for the removal of chlorogenic acid polyphenol (CGA) from aqueous solutions. Due to the hydrophilic nature of hydrotalcite, the adsorbent was functionalized with hexadecyltrimethylammonium bromide (CTAB) to increase its affinity for CGA, resulting in a removal efficiency of approximately 96%. Composite fiber membranes were prepared by solution-blowing spinning with specific amounts of hydrotalcite added (i.e., 1 to 60 wt%). A 3:1 PCL:PMMA blend resulted in superior mechanical traction (0.8 MPa) and stress deformation (70%) compared to pure PCL (0.7 MPa and 37%) and PMMA (0.1 MPa and 5%) fibers. PCL:PMMA membranes with 60% LDH-CTAB exhibited CGA removal rates equal to 55% in the first cycle while maintaining the capacity to remove 30% of the polyphenol after five consecutive reuses. Removal rates up to 90% could also be achieved with an appropriate adsorbent dose (2 g L−1). Adsorption was found to follow pseudo-second-order kinetics and was adequately described by the Langmuir model, saturating LDH-CTAB active sites in four hours. PCL:PMMA:LDH-CTAB composites can be considered a potential alternative to support adsorbents for water remediation.
Keywords: adsorption; chlorogenic acid; composite; hydrotalcite; polyphenol; solution blowing spinning